Answer:
45) The function corresponds to graph A
46) The function corresponds to graph C
47) The function corresponds to graph B
48) The function corresponds to graph D
Step-by-step explanation:
We know that the function f(x) is:
![f(x)=(x-2)^{2}+1](https://tex.z-dn.net/?f=f%28x%29%3D%28x-2%29%5E%7B2%7D%2B1)
45)
The function g(x) is given by:
![g(x)=f(x-1)](https://tex.z-dn.net/?f=g%28x%29%3Df%28x-1%29)
using f(x) we can find f(x-1)
![g(x)=((x-1)-2)^{2}+1=(x-3)^{2}+1](https://tex.z-dn.net/?f=g%28x%29%3D%28%28x-1%29-2%29%5E%7B2%7D%2B1%3D%28x-3%29%5E%7B2%7D%2B1)
If we take the derivative and equal to zero we will find the minimum value of the parabolla (x,y) and then find the correct graph.
![g(x)'=2(x-3)](https://tex.z-dn.net/?f=g%28x%29%27%3D2%28x-3%29)
![2(x-3)=0](https://tex.z-dn.net/?f=2%28x-3%29%3D0)
Puting it on g(x) we will get y value.
![y=g(3)=(3-3)^{2}+1](https://tex.z-dn.net/?f=y%3Dg%283%29%3D%283-3%29%5E%7B2%7D%2B1)
![y=g(3)=1](https://tex.z-dn.net/?f=y%3Dg%283%29%3D1)
<u>Then, the minimum point of this function is (3,1) and it corresponds to (A)</u>
46)
Let's use the same method here.
![g(x)=f(x+2)](https://tex.z-dn.net/?f=g%28x%29%3Df%28x%2B2%29)
![g(x)=((x+2)-2)^{2}+1](https://tex.z-dn.net/?f=g%28x%29%3D%28%28x%2B2%29-2%29%5E%7B2%7D%2B1)
![g(x)=(x)^{2}+1](https://tex.z-dn.net/?f=g%28x%29%3D%28x%29%5E%7B2%7D%2B1)
Let's find the first derivative and equal to zero to find x and y minimum value.
![g'(x)=2x](https://tex.z-dn.net/?f=g%27%28x%29%3D2x)
![0=2x](https://tex.z-dn.net/?f=0%3D2x)
![x=0](https://tex.z-dn.net/?f=x%3D0)
Evaluatinf g(x) at this value of x we have:
![g(0)=(x)^{2}+1](https://tex.z-dn.net/?f=g%280%29%3D%28x%29%5E%7B2%7D%2B1)
![g(0)=1](https://tex.z-dn.net/?f=g%280%29%3D1)
<u>Then, the minimum point of this function is (0,1) and it corresponds to (C)</u>
47)
Let's use the same method here.
![g(x)=f(x)+2](https://tex.z-dn.net/?f=g%28x%29%3Df%28x%29%2B2)
![g(x)=(x-2)^{2}+1+2](https://tex.z-dn.net/?f=g%28x%29%3D%28x-2%29%5E%7B2%7D%2B1%2B2)
![g(x)=(x-2)^{2}+3](https://tex.z-dn.net/?f=g%28x%29%3D%28x-2%29%5E%7B2%7D%2B3)
Let's find the first derivative and equal to zero to find x and y minimum value.
![g'(x)=2(x-2)](https://tex.z-dn.net/?f=g%27%28x%29%3D2%28x-2%29)
![0=2(x-2)](https://tex.z-dn.net/?f=0%3D2%28x-2%29)
![x=2](https://tex.z-dn.net/?f=x%3D2)
Evaluatinf g(x) at this value of x we have:
![g(2)=(2-2)^{2}+3](https://tex.z-dn.net/?f=g%282%29%3D%282-2%29%5E%7B2%7D%2B3)
![g(2)=3](https://tex.z-dn.net/?f=g%282%29%3D3)
<u>Then, the minimum point of this function is (2,3) and it corresponds to (B)</u>
48)
Let's use the same method here.
![g(x)=f(x)-3](https://tex.z-dn.net/?f=g%28x%29%3Df%28x%29-3)
![g(x)=(x-2)^{2}+1-3](https://tex.z-dn.net/?f=g%28x%29%3D%28x-2%29%5E%7B2%7D%2B1-3)
![g(x)=(x-2)^{2}-2](https://tex.z-dn.net/?f=g%28x%29%3D%28x-2%29%5E%7B2%7D-2)
Let's find the first derivative and equal to zero to find x and y minimum value.
![g'(x)=2(x-2)](https://tex.z-dn.net/?f=g%27%28x%29%3D2%28x-2%29)
![0=2(x-2)](https://tex.z-dn.net/?f=0%3D2%28x-2%29)
![x=2](https://tex.z-dn.net/?f=x%3D2)
Evaluatinf g(x) at this value of x we have:
![g(2)=(2-2)^{2}-2](https://tex.z-dn.net/?f=g%282%29%3D%282-2%29%5E%7B2%7D-2)
![g(2)=-2](https://tex.z-dn.net/?f=g%282%29%3D-2)
<u>Then, the minimum point of this function is (2,-2) and it corresponds to (D)</u>
<u />
I hope it helps you!
<u />